Study on hierarchical regulation of crop irrigation threshold under severe drought conditions - Ruidan Gu; Huaxiang He; He Chen; Jiake Tian (Agricultural Water Management)
The increased frequency of severe drought events has increased the global water supply security risks, posing a substantial threat to food crop yields such as rice. Therefore, it is crucial to accurately regulate rice irrigation thresholds and optimize the coordination between rice irrigation and the water demand of other industries under severe drought conditions. This study employed the WOFOST model to simulate rice yield in Chuxiong Yi Autonomous Prefecture, Yunnan Province, under various irrigation scenarios, focusing on severe drought conditions. Optimal irrigation schemes and corresponding irrigation thresholds were determined for different yield reduction rates during 90 % and 95 % extremely dry years, utilizing predefined rates of irrigation contribution, yield reduction, and water productivity. The results are as follows. (1) During extremely dry years, irrigation during the jointing-booting, heading-flowering stages can boost the yield by up to 218 % and 270 % compared to the yield without irrigation, respectively. Based on irrigation water productivity, it can be advisable to avoid reducing irrigation during the jointing-booting stage and heading-flowering stage. (2) The irrigation threshold varied according to the severity of drought. (3) During three consecutive years of severe drought, rice yield exhibited an annual decreasing trend, aiming to minimize comprehensive economic losses and optimize water utilization efficiently. This study can provide decision support for the hierarchical regulation of crop irrigation thresholds under severe drought conditions.